Description of the female, redescription of the male, and host associations of the Nearctic species Sphaeropthalma jacala Schuster (Hymenoptera: Mutillidae) - Pitts, James P.; Parker, Frank D. (Zootaxa, 2005)
Sphaeropthalma jacala Schuster, the sole member of the S. jacala species-group, was reared from Trypoxylon, Centris, and Chrysis cocoons collected in Jalisco, Mexico. These are the first host records for this species. This material has also generated a new sex association and the female of S. jacala is described. The male is redescribed based on this new material and illustrations are given for both sexes.